The Teaching Profession : Present and Future - Reis Monteiro, A. (SpringerBriefs in Education, 2015)
This volume contributes to debates about the teaching profession by reviewing international and national reports on its status, as well as on reforms of various education systems. It proposes a global approach to the quality of the teaching profession as a decisive ingredient of education quality, including a conception of its identity and a vision of its future. Moreover, it is suggested that professional self-regulation may be the best way to achieve higher professional and social status for teachers, since it allows educators collectively to assume the culture of the values that comprise the uniqueness and fullness of the teaching profession.